Robust Portfolio Mean-Variance Optimization for Capital Allocation in Stock Investment Using the Genetic Algorithm: A Systematic Literature Review - Diandra Chika Fransisca; Sukono; Diah Chaerani; Nurfadhlina Abdul Halim (MDPI, 2024)
Indexed by WOS/ Scopus